MENGKAJI PESAN DAKWAH DALAM PROGRAM RELIGI DI TELEVISI DIGITAL - Roni Tabroni; Ahmad Rifai; Agung Tirta Wibawa; Detyani Aulia Malik; Ziyan Dini Hunafa (Balai Diklat Keagamaan Bandung, 2023)
This study looks into religious programming in digital broadcasting facilities following the analog switch-off (ASO). Local television in West Java, specifically SMTV and MQTV, which have transitioned from analog to digital, is the subject of this study. The goal of this study is to examine how religious programming has changed on both televisions after they went digital. With a case study methodology, this research is qualitative. Three methods of data collection are used: direct interviews with television executives, observation, and monitoring the broadcast's content. According to the study's findings, switching to digital actually has a number of advantages, including improved picture and sound quality, more viewers, longer broadcast hours, and more effective funding. Both SMTV and MQTV acknowledge that there has been a rise in religious programming. Religious programming fills the extra time according to the leadership's policy of broadcasting 24 hours a day. Islamic and Christian religious lectures have been added to SMTV as a regular daily, weekly, and monthly program. The different Sundanese cultural arts shows on SMTV always feature religious material. MQTV also incorporates religious programming to enhance its reputation as a heartwarming Islamic television station. Religious programming comes in a wide range of formats, including monologue lectures, chat shows, consultations, and reality shows. The varied packaging are designed to prevent religious content from coming out as repetitive and dull.Keywords: broadcast; religious; digital; Analog Switch-off